Community perspectives on spinal cord injury in rugby union: facts and fears - Merrick, N.; Badenhorst, M.; Morgan, A.; Fortington, L. (Science and Medicine in Football, 2025)
Introduction: The sport of rugby union, henceforth rugby, is associated with a risk of spinal cord injury (SCI). Perceived risks can impact participation. Understanding community perspectives on rugby-related SCI may provide insight for addressing concerns around risk. The aim of this study was to explore community perspectives through social media discussion about SCI in rugby union. Methods: Posts about SCI in rugby union were identified using the advanced search function on Twitter. Data (content as original post, retweet, quote tweet and comments) were included if focused on Rugby Union and written in English. Inclusion dates (July 2018 to June 2019) were chosen to capture a period when several SCI (n = 4) occurred in community rugby in Australia. Data were analysed using a thematic approach. Results: Four themes were derived from the collected data. The `pendulum swing` relates to the disparate views of rugby, from being overly cautious to too dangerous to play. The `role of rugby culture` described engrained behaviours and attitudes on and off-field toward safety. `Media influence` describes the emotive narrative used when reporting rugby-related SCI. `After the injury` looks at expressions of sympathy and inspiration. These findings showed how individuals` views of SCI were influenced through rugby culture, trust in governing bodies and the news media. Conclusion: By `listening in` to community views, their most pertinent safety concerns can be addressed. Both facts and fears on rugby-related SCI were evident, and these extreme views can be balanced with evidence-based education and sensible risk management.